Penerapan Pembelajaran Mendalam Melalui Joyful, Meaningful, dan Mindful Learning: Tinjauan Literatur - Feri, Muhammad (IBTIDA-Jurnal Kajian Pendidikan Dasar, 2025)
This study explores the application of deep learning approaches in primary education through a literature review. The research aims to examine how deep learning characterized by joyful, meaningful, and mindful learning can be implemented to foster holistic student development. Utilizing the PRISMA framework, relevant national and international publications from 2014 to 2024 were reviewed and analyzed. The results indicate that while the term “deep learning” is often associated with technology and artificial intelligence, its pedagogical meaning centered on Fullan’s 6Cs frameworki s still underutilized in classroom practice. Key obstacles to implementation include limited teacher training, rigid curricula, inadequate facilities, and resistance to change in educational mindsets. Despite these challenges, deep learning offers significant potential to cultivate critical thinking, empathy, collaboration, and lifelong learning in students. The study concludes that a shift in perspective is needed, urging educators to adopt and adapt deep learning strategies in alignment with student needs and future educational demands.